Social influences on expressed willingness to pay: results of a deliberative monetary valuation study in Colombia. Issue 9 (2nd September 2017) - Vargas, Andrés; Lo, Alex Y.; Rohde, Nicholas; Howes, Michael
Abstract : Deliberative monetary valuation (DMV) methods can support environmental decision making by enabling the exchange of arguments and information to produce more democratic outcomes. The product of a valuation may be an array of expressions of willingness to pay (WTP) by individuals or a collectively agreed monetary value. Concerns have been raised, however, as to whether this product is an outcome of thoughtful and independent decision-making or influenced by social pressures to conform. Our study examines this issue and addresses concerns about the use of DMV, based on a public deliberation of forest conservation in Colombia. We analyzed the impacts of social conformity on WTP under two different decision scenarios: individual and collective. The results suggest that the impacts of social conformity are greater when a collective decision is required. These findings indicate that tensions between the differing goals of DMV could undermine its democratic promise.